PENGARUH CUSTOMER VALUE TERHADAP CUSTOMER SATISFACTION PADA ONLINE TRAVEL AGENT TIKET.COM - Rahman Fauzi; Kusumawardhani, Nuruni Ika (JWM (JURNAL WAWASAN MANAJEMEN), 2024)
When customers receive a product or service from a business and they receive high value, then all problems thatarise between customer expectations and the actual product or service will be resolved. Currently, the aim of thisresearch is to determine whether customer value—defined as functional, emotional, and social value—has animpact on customer satisfaction related to the online travel agent Tiket.com. The type of analysis used wasquantitative analysis with a total of 104 respondents who met the sample criteria. Sample collection was carriedout using the Purposive Sampling technique combined with the Non Probability Sampling method. Data analysisin this study used SEM (Structural Equation Modeling) techniques based on PLS (Partial Lest Square). Researchfindings show that functional, emotional and social values have a significant and positive impact on customersatisfaction at online travel agent Tiket.com.Keywords: Customer Satisfaction, Customer Value, Emotional Value, Functional Value, Social Value